The predictors of malignancy in thyroid nodules with atypia of undetermined significance or follicular lesions of undetermined significance (Annals of Medical Research, 2021)
Aim: This study aimed to evaluate clinical, radiological and laboratory (neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios, and mean platelet value) features that may better define the rate of malignancy in order to contribute to the management of thyroid nodules with AUS/FLUS.Material and Methods: The data of patients with histologic findings of AUS/FLUS on FNA, who underwent surgery at General Surgery Department in a tertiary care hospital between January 2012 and December 2019, were reviewed retrospectively. The patients with any other malign and/or inflammatory diseases and continued on corticosteroid therapy and/or chemotherapy were excluded.Results: The current study included 60 patients (73.3% women), who underwent surgery for 62 thyroid nodules classified as AUS/FLUS. The specimen pathology revealed a thyroid malignancy in 16 patients, including 10 patients with papillary cancer, 5 patients with micro-papillary thyroid cancer, 1 patient with minimally invasive follicular carcinoma. Ten patients had follicular adenoma. The remaining 35 patients (37 nodules) had nodular colloidal hyperplasia and/or chronic lymphocytic thyroiditis. The rates of malignancy (ROM) and neoplasia (RON) were 25.8% and 40.3%, respectively. Nearly half of the cases (41.9%) had chronic lymphocytic thyroiditis. The malignancy rate in cases with chronic lymphocytic thyroiditis was 26.9%, which was similar in cases without (25%). In multivariate analysis, only microcalcifications were found to be positively associated with malignancy (p: 0.1; [OR] 5.185; CI95% 1.4-19.18). Conclusion: Chronic lymphocytic thyroiditis may lead to overestimation of AUS/FLUS results. It was not associated with malignancy in thyroid nodules with AUS/FLUS. Inflammatory values, such as NLR, PLR and MPV, were not useful markers of malignancy. Among all variables only US findings (microcalcifications according to the current study) may be useful in risk-stratification of malignancy in thyroid nodules with AUS/FLUS.
Keywords: AUS; indeterminate nodule; fine needle aspiration; FLUS; FNA; NLR; PLR; thyroid malignancy; thyroid nodule